(untitled) (The Review of Diabetic Studies, 2025)
Drugs may degrade chemically or physically, changing their therapeutic usefulness or possibly having harmful side effects. Degradation products were discovered and degradation patterns were suggested using mass spectrometry. The optimized chromatographic setup used a CHEMSIL ODS-C18 column (250 mm × 4.6 mm, 5 μm). The mobile phase consisted of Phase A (Methanol: Acetonitrile: Water, 70:15:15). The flow rate was maintained at 1 mL/min, detection was carried out at 263 nm. The Limit of Quantization (LOQ) for all degradation impurities was found to be 0.05%, matching the reporting threshold. Therefore, the novel method showed to be linear from range 5-30 µg/ml, with high precision (CV < 2%) and accuracy (recuperation of 99.82%). It is simple and reliable, free of placebo interferences. Darunavir was more vulnerable to degradation when exposed to acid, alkali, and peroxide, as evidenced by the degradation products that were found. However, under photolytic and thermolytic conditions, no discernible deterioration effects were found. The HPLC method was able to quantify Darunavir and its degradation products. This study is novel because it identifies the variables that influence the stability of Darunavir hydrate in tablets, which is the first step in determining the degradation products. In low doses when linearity is present, the drug and the primary degradation products can be monitored using the new stability-indicating technique.